Structural characterizations of copper incorporated manganese oxide OMS-2 material and its efficiencies on toluene oxidation. Issue 4 (3rd April 2022) - Kaewbuddee, C.; Chirawatkul, P.; Kamonsuangkasem, K.; Chanlek, N.; Wantala, K.
Abstract: This work aimed to study the excellent properties of the high-valent copper doped into the framework structure of K-OMS-2 catalyst (Cu-K-OMS-2). The physicochemical properties of Cu-K-OMS-2 material were examined by many techniques. The copper dopant can improve the physicochemical properties of the K-OMS-2 catalyst, including the specific surface area, Oads /Olatt ratio, and Cu 3+ /Cu 2+ ratio, resulting in enhanced catalytic activity. The specific surface area of Cu-K-OMS-2 was higher than K-OMS-2 material. The Mn 3+ /Mn 4+ ratio of K-OMS-2 (0.10) was decreased, compared with the Cu-K-OMS-2 (0.08) catalyst. Moreover, the copper dopant can enhance the Oads /Olatt ratio of Cu-K-OMS-2 to 0.62, which higher than K-OMS-2 (0.24). The Cu 3+ species were observed in the Cu-K-OMS-2 structure. Besides, the oxidation state of copper on the Cu-K-OMS-2 surface revealed both Cu 3+ and Cu 2+ species, which affected toluene removal. The existence of the Cu 3+ /Cu 2+ ratio led to enhance toluene removal at the low reaction temperature. Moreover, the Cu K-edge EXAFS spectrum demonstrated that the Cu ions existed in the same site as the Mn ions in the K-OMS-2 framework structure. Consequently, we can propose that Cu 3+ existed in the Cu-K-OMS-2 framework structure, which influenced the high toluene oxidation at the low reaction temperature. The H2 -TPR results confirmed that the copper dopant could improve the reducibility and enhance oxygen mobility of K-OMS-2 material at the low reaction temperature. Also, the high-valent copper doped into the K-OMS-2 catalyst showed high stability for VOCs oxidation. The activation energy of toluene oxidation over the Cu-K-OMS-2 catalyst was about 91.18 kJ mol −1 .